ANALISIS PENYUSUNAN DAN PELAKSANAAN ANGGARAN OLEH SEKRETARIAT DPRD KABUPATEN JEPARA - Sulistiyono, Zulkifli; Nugraheni, Agustina Prativi (Transpublika Publisher, 2022)
In leading the government, the aspirations of the people are needed to carry out development. The Regional People's Representative Council (DPRD) is a government body that can hear about the problems of the people in an area. In carrying out regional development, the DPRD and the Government have an important role in the budgeting process. The process of preparing an effective and efficient budget can produce a budget that is in line with the needs in the period concerned. Budgeting is an important system to achieve an effective and efficient budget when in its implementation. The purpose of this study is to analyze the process of budgeting and budget implementation in the Secretariat of the Jepara Regency DPRD. This research method uses descriptive analysis through observation and interviews. The DPRD Secretariat is a regional device performance unit that is responsible to the Dprd Leadership operationally and is responsible to the Regent in administrative matters. In the process of budgeting, the Government and dprd agreed to draw up a budget based on performance. Performance-based budgets prioritize on the output of the implementation of activities achieved related to the use of planned budgets.